A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Yang, Sun-Rong; Yao, Le; Hou, Zhang-Shuai; Ye, Xun-Yan; Li, Ying; Huang, Xing; Shen, Shu-Zhong; Wang, Xiang-Dong (Palaeoworld, 2024)
The Pennsylvanian rugose corals are not well understood in Northwest China due to their low diversity and restricted distribution under the impact from coeval Gondwana glaciation. In this study, nine rugose coral species of eight genera are described from the Shiqiantan and Jingou formations (Moscovian to Kasimovian stages) in the new Shuangjingzi Section, northern Xinjiang, Northwest China. These species include dissepimented solitary rugose corals (Arctophyllum shuangjingziense n. sp., Arctophyllum intermedium, Caninophyllum ürümqiense, Gshelia qitaiensis, Pseudotimania aff. junggarensis, Pseudozaphrentoides paramapingensis), and non-dissepimented solitary corals (Amplexizaphrentis sp., Bradyphyllum bellicostatum and Hapsiphyllum sp.). This coral assemblage includes local taxa of the Junggar Basin, with a few common elements from Urals Mountains, Novaya Zemlya, and Spitsbergen in northwestern Palaeotethys Ocean. The composition of the Shuangjingzi corals is characterized by the medium-large dissepimentarium Caninophyllum ürümqiense-Gshelia qitaiensis assemblage, indicating open shallow carbonate environments. Compared with the Shiqiantan Formation, the obvious increase in the abundance of narrow-dissepimentarium corals of Gshelia in the upper Jingou Formation, implies that low-energy environments could have developed, with an increase of shales in this interval.